Suppression of corrosion on stainless steel 303 with automatic impressed current cathodic protection (a-ICCP) method in simulated seawater - Hamsir; Sutresman, Onny; Arsyad, Hairul; Syahid, Muhammad; Widyianto, Agus (Eastern-European Journal of Enterprise Technologies, 2022)
One effective method to slow down metal corrosion rate is the impressed current cathodic protection (ICCP) system. The ICCP system is suitable for coastal applications such as piping systems and offshore structures. In this application, metal surfaces tend to be exposed to seawater. Specific concentrations of seawater can accelerate the occurrence of corrosion of metals, even though they are stainless steel types. This study applied the automatic ICCP system to stainless steel 303. Stainless steel 303 will be immersed in simulated seawater at several concentrations of NaCl (27 ppt, 31 ppt, and 35 ppt). The specimens were immersed in NaCl solution for three weeks or about 504 hours at a constant temperature of 38 °C. After the sample has been soaked, quantitative and qualitative measurements were carried out. Quantitative measures include average weight loss, corrosion rate, and potential value. At the same time, the qualitative measurements include macroscopic, Scanning Electron Microscopy (SEM), and Energy Dispersive X-Ray Spectroscopy (EDS). Based on quantitative measures, it was found that the difference in average weight loss and corrosion rate for each NaCl concentration was not very significant. The difference of each parameter is less than 0.1 % and 0.22 %, respectively. The potential value quickly reaches a steady state at NaCl concentrations of 27 ppt and 31 ppt in less than 10 seconds. The results of the SEM test showed a change in the metal structure. The oxygen (O) content in the metal after the EDS test showed a decrease in this element up to 35 % at a NaCl concentration of 35 ppt. The decrease in oxygen (O) can slow down the corrosion rate in metals when exposed to seawater.